Determination of Oxidative Stress Parameters and Tissue Factor Activity in the Saliva of Patients with Periodontitis - (:unkn) unknown (My University, 2019)
Objective: Periodontitis, an inflammatory disease, leads to the destruction of the periodontium and results in tooth loss.Reactive oxygen species are involved in the destruction of periodontal tissues and systemic inflammation. The aim of thestudy was to evaluate and compare the oxidative status in different kinds of periodontal disease and whether the treatmentamends these effects.Materials and Methods: Whole saliva was collected from 30 patients with chronic marginal gingivitis, chronic periodontitisand generalized aggressive periodontitis at baseline and after non-surgical periodontal therapy and 10 healthy controlsubjects. Lipid peroxidation (LPO) and glutathione (GSH) levels and glutathione-s-transferase, superoxide dismutase catalaseand tissue factor (TF) activities were determined in the whole saliva.Results: Antioxidant enzyme activities were significantly higher in periodontitis groups before non-surgical periodontaltherapy and also increased LPO levels and decreased TF activities were found in these groups. Significant decreases inantioxidant enzymes and LPO levels, and increases in TF activities were detected after treatment. GSH levels increased aftertreatment.Conclusion: Increased antioxidant enzyme activities and LPO levels indicate destruction of periodontal tissues due toexcessive radical production. Treatment of periodontitis and restoring the balance of oxidant-antioxidants ameliorates tissuedamage caused by oxygen species and inflammation.
Keywords: Biyoloji